Spoiler groups and UN peacekeeping - Nadin, Peter; Cammaert, Patrick; Popovski, Vesselin (Adelphi (Series) (International Institute for Strategic Studies), 2015)
"UN peacekeepers today do far more than patrol a ceasefire line. In most cases, there is no frontline, no truce, numerous parties and among them some armed groups seeking to undermine a settlement. In short, the UN is attempting to conduct peacekeeping in places where there is no peace to keep. Unfortunately the UN has failed to adequately develop the instruments to identify armed groups, and then deal with the challenge they pose. This book is a policy guide for UN missions. It analyses the nature of non-permissive UN mission environments and argues that the UN should think afresh about its approach to missions in these settings. By embracing and developing three concepts -- robust peacekeeping, political processes, and the protection of civilians -- the UN can arrive at a stabilisation doctrine"--Back cover